Investigation into the Pore Structure and Multifractal Characteristics of Shale Reservoirs through N2 Adsorption: An Application in the Triassic Yanchang Formation, Ordos Basin, China. (27th October 2021) - Liang, Zhikai; Jiang, Zhenxue; Li, Zhuo; Gao, Fenglin; Liu, Xiaoqing
Abstract : To understand the pore structure and heterogeneity of pore size distribution (PSD) is essential for revealing fluid mechanics and evaluating the utilization of unconventional resources. In this study, there are multiple shale examples collected from the Chang 7 section in the Ordos Basin for the investigation was conducted on the basis of various experiments on total organic carbon (TOC), X-ray diffraction (XRD), and nitrogen gas adsorption, through scanning electron microscopy (SEM) and multifractal method. The multifractal characteristic parameters, including the width of singularity spectra (Δ α ), Hurst exponent (H ), D 1 / D 0, and nitrogen gas adsorption, were used to find out about the characteristics of pore development and to quantify the complexity and heterogeneity of pore structure. Depending on the exact mineral composition, the Yanchang Formation of Chang 7 shales is classified into either silty mudstone (SM) or muddy siltstone lithofacies (MS). According to the investigative results, the Chang 7 lacustrine shale features a complex pore system with the pores ranging from 1.5 to 10 nm in diameter. Besides, mesopores contribute significantly to the total pore volume (TPV) and total surface area (TSA). As for TPV and TSA of the SM lithofacies in the samples under investigation, they are nearly 1.09–1.78 and 0.80–1.72 times greater as compared to the MS lithofacies samples. The dominant types of reservoir spaces include organic matter (OM) pore and interparticle pore which are related to inorganic minerals. The value of Δ α is higher for MS lithofacies than for SM lithofacies, indicating a greater heterogeneity of PSD in the MS lithofacies. The pore structure of MS lithofacies is determined mainly by TOC and siliceous mineral content, whereas the influencing factors for SM lithofacies are TOC and clay mineral content. There is a significant relationship between multifractal parameters and pore structure parameters for both SM and MS lithofacies. The TOC of SM and MS lithofacies exhibits a close correlation with Δ α, suggesting that the pores in organic matter are dominated by those nanopores with a complex and heterogeneous pore structure. The rock composition of the lithofacies can affect Δ α to a varying extent, which means that the minerals have an evident impact on the heterogeneity of MS and SM lithofacies.